A Social Norms-Based Intervention Improves Diet Diversity Among Women of Reproductive Age in Rural Odisha, India: The RANI Project. (7th June 2021) - Talegawkar, Sameera; Jin, Yichen; Sedlander, Erica; Ganjoo, Rohini; Behera, Satyaranjan; DiPietro, Loretta; Rimal, Rajiv
Abstract: Objectives: To investigate the effect of a social norms-based intervention on diet diversity among women of reproductive age. Methods: Data from the Reduction in Anemia through Normative Innovations (RANI) Project were used. Up to three contiguous villages in Odisha, India were assigned to clusters, which were then randomized into treatment or control arm. Within each cluster, homes were randomly chosen in proportion to cluster size and one woman of reproductive age was randomly chosen from each selected home (N = 3797). The RANI intervention is based on the theory of normative social behavior and includes: participatory learning modules coupled with games; short videos shown to participating women and their families; and monthly hemoglobin testing followed by community discussion. Exposure to the intervention was assessed by the frequency of viewing images from the participatory learning modules, number of videos seen, and number of hemoglobin tests taken. Diet diversity was assessed by the Food and Agriculture Organization's Minimum Dietary Diversity for Women (MDD-W, score ranging 0–10 with MDD-W score ≥ 5 considered to represent a diverse diet). Multiple logistic regression examined the effect of exposure to the intervention on diet diversity. Results: Compared to baseline, diet diversity score increased in both treatment and control groups by 13% and 8%, respectively. The odds of having a diet diversity score ≥ 5 was 47% higher in treatment group than the control group ( P  < .001). Higher exposure to participatory learning modules was associated with higher odds of having a diet diversity score ≥ 5 ( P  < .001), and participation in learning module games was associated with 40% higher odds of having a diverse diet ( P  < .001). Watching short health communication videos increased the odds of having a diverse diet ( P  < .001), and women who took more hemoglobin tests as part of the RANI intervention had higher odds of having a diverse diet ( P  < .001). Conclusions: Being in the RANI intervention improved women's diet diversity scores, indicating that the social norms-based intervention, albeit without food or iron supplementation, was effective in improving diet quality among women of reproductive age living in rural India. Funding Sources: This study was supported by a grant from The Bill and Melinda Gates Foundation.